Electrolyte Additive-Assembled Interconnecting Molecules–Zinc Anode Interface for Zinc-Ion Hybrid Supercapacitors - Yang Li; Xu Li; Xinya Peng; Xinyu Yang; Feiyu Kang; Liubing Dong (Nano-Micro Letters)
Highlights An important topic about zinc-ion hybrid supercapacitors is proposed, i.e., how to achieve not only ultrastable but also fast-kinetics zinc anodes to match capacitive cathodes featuring ultralong cycle life and fast charge storage ability. An electrolyte additive-assembled interconnecting molecules–zinc anode interface is proposed, and its regulation mechanisms on zinc plating/stripping behaviors are revealed. A scalable strategy is reported for achieving highly stable and fast-rate zinc anodes toward zinc-based electrochemical energy storage systems.